2018
DOI: 10.1093/jee/toy173
|View full text |Cite
|
Sign up to set email alerts
|

Mobility of Adult Tribolium castaneum (Coleoptera: Tenebrionidae) and Rhyzopertha dominica (Coleoptera: Bostrichidae) After Exposure to Long-Lasting Insecticide-Incorporated Netting

Abstract: Stored products represent an enormous economic output, but insects regularly immigrate into stored products from the surrounding landscape throughout the postharvest supply chain. Long-lasting insecticide-incorporatednetting (LLIN), which usually contains an incorporated pyrethroid, has been used as part of a strategy to reduce the spread of malaria in tropical regions since the 1990s and has only recently been considered for its application in pre- and postharvest agricultural contexts. The goal of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…However, for each species, there were substantial reductions in movement even at exposure to low concentrations of the insecticide. This suggests that dispersal from the treated area will be minimal, and these individuals will likely not be able to colonize new areas of a food facility (e.g., including perhaps adjacent grain bins), as has been documented by exposure of T. castaneum and R. dominica to a long-lasting, deltamethrin-incorporated netting material [16]. Understanding movement after exposure provides a more comprehensive picture of the efficacy for chemical control tactics, with clear management implications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, for each species, there were substantial reductions in movement even at exposure to low concentrations of the insecticide. This suggests that dispersal from the treated area will be minimal, and these individuals will likely not be able to colonize new areas of a food facility (e.g., including perhaps adjacent grain bins), as has been documented by exposure of T. castaneum and R. dominica to a long-lasting, deltamethrin-incorporated netting material [16]. Understanding movement after exposure provides a more comprehensive picture of the efficacy for chemical control tactics, with clear management implications.…”
Section: Discussionmentioning
confidence: 99%
“…One adult from each concentration was placed individually into six filter paper-lined (Whatman #1, GE Healthcare, Chicago, IL, USA) 62 cm 2 Petri dishes, where movement (distance moved and instantaneous velocity) was recorded using a video-tracking apparatus combined with Ethovision XT v. 14.0 (Noldus Software, Leesburg, VA, USA). The apparatus was described in detail in Morrison et al [16] Briefly, a network camera (Basler AG, Ahrensburg, Germany) suspended 80 cm above the insects recorded the movement of each adult for 10 min, after which the dishes were removed, and the insects were discarded. This process was repeated four more times per replicate, with a total of n = 15 insects tested per treatment combination.…”
Section: Insecticide Assaymentioning
confidence: 99%
See 2 more Smart Citations
“…By using these two types of hostile matrix, these authors found that: (a) A higher angle of the connecting tube, i.e., a more difficult dispersal path, lowered the dispersal success of males and females of T. castaneum, and (b) the increased length of the tubes connecting the containers increased the duration necessary for reaching the terminal (destination) container. Morrison et al [79] modified the Arnold's et al [72] system by working with two containers whose distance was increased (25, 75, and 175 cm) in order to investigate the effects of short exposures to pyrethroid (long-lasting insecticide-incorporated netting) on the dispersal capabilities of two insect species. For control insects, the matrix was slightly hostile for the red flour beetle, with fewer insects reaching the destination containers when the distance in between the two containers was the highest (175 cm), as compared with the two other tested distances.…”
Section: Source Containermentioning
confidence: 99%